Drought indices supporting drought management in transboundary watersheds subject to climate alterations - Al-Faraj, Furat A. M.; Scholz, Miklas; Tigkas, Dimitris; Boni, Martino (Water policy, 2015)
There is growing concern in Iraq about the inefficiency of reactive drought management practices. Corresponding actions are largely characterized as emergency-based responses that treat the symptoms of drought rather than consider the vulnerability components associated with impacts. The Diyala watershed shared between Iraq and Iran has been used as an example transboundary river basin marked by ineffectiveness of drought management. The standardized precipitation index and the reconnaissance drought index were used to determine the historical meteorological drought episodes and analysis indicated climate change-induced alterations in the area. Spatiotemporal drought maps were drawn, which can be used for the identification of drought prone areas and assist with proactive planning. This paper discusses the underlying causes of the impairments of drought management policies, and the challenges and difficulties accompanying the governance of drought in Iraq. Given the influence of climate change and the upstream anthropogenic pressures, the time has come to adopt a gradual nation-wide transition step to drought risk planning incorporating a management approach at the transboundary scale. Moreover, the institutional and technical water vulnerability components associated with drought management should be considered in an integrated manner. The paper presents a generic technical template to support decision-makers in drought risk management.